Effect of Some Ecological Factors on Earthworms (Lumbercus terrestris) in Wasit Governorate - Jamil, Hussein Ali; Jabour, Hamza Jabbar; Chachain, Nebrass Faleh (South Eastern European Journal of Public Health, 2024)
Monthly earthworm samples were collected from two locations in Suwairah City‎ of Wasit Governorate. where the first location was northwest of the district and is characterized by an abundance of citrus trees such as orange, lemon and Punica granatum as well as many palm trees of different types, the second area is characterized by an abundance of vegetable plants like Cauliflower, Allium cepa, and Brassica oleracea. Soil temperature, moisture, pH, texture and organic matter levels were measured at all sample sites. Soil temperature ranged between 11C° to 50C° as recorded during February and August respectively. The values of PH have ranged between 6.8 to 8.0. Soil moisture and Organic matter content were highest in Region (B) samples, 40% and 6.6% respectively. However, lowest organic matter and soil moisture percentage were 17% and 3.13% recorded at in Region (A) samples respectively. All sites were characterized by loamy acidic reactive soils.